The Influence of Electronic Word of Mouth in Social Media on Yemeni Consumers' Purchase Intentions - Ali, Omar Hasan Mansoor; Al-Maqtari, Aayed Qassem Hassan (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
As a leading source of consumer knowledge, eWOM has been expanding and diversifying across various formats and platforms; yet social media has proven to be an especially effective platform for eWOM and remains one of the most significant sources of information. This study, therefore, reinforces the existing body of knowledge related to the impact of eWOM on consumer purchasing intentions in least developed countries. The main purpose of this study is to investigate the influence of eWOM in SM determinants (i.e., altruism, tie strength, information credibility, needs of information, attitude towards information, and information adoption) on purchase intentions. To do so, the study employed convenience sampling, concentrating on Yemeni participants aged (18) and above who engage in social media. Online survey invitations were disseminated over various social media platforms. A total of 428 questionnaires were collected; yet only (344) were usable for statistical analysis using SPSS (27) and Jamovi (2.3). The findings indicated that Yemeni consumers demonstrated favourable impressions of eWOM in SM and recognised its significant role in altering their purchase intentions. The results of path analysis within the SEM indicated that altruism, needs of information, attitudes towards information, and information adoption exert positive effects on purchase intentions.